PENGARUH DUKUNGAN KELUARGA TERHADAP FREKUENSI KEKAMBUHAN KLIEN SKIZOFRENIA DI IGD RUMAH SAKIT JIWA DAERAH SURAKARTA - Titik Anggraeni Anggraeni; Sri Sayekti Heni Sunaryanti Akademi Keperawatan Mamba’ul ‘Ulum Surakarta (Jurnal Kebidanan, 2010)
PENGARUH DUKUNGAN KELUARGA TERHADAP FREKUENSI KEKAMBUHAN KLIEN SKIZOFRENIA DI IGD RUMAH SAKIT JIWA DAERAH SURAKARTA Titik Anggraeni & Sri Sayekti Heni Sunaryanti Akademi Keperawatan Mamba’ul ‘Ulum Surakarta ABSTRACT Relapsing represent the appearance occurence return the sign and symptom, though client still experience the medication program. Family have various function in prevention of soul trouble, among other things by showing empathy and also lift a hand to natural family member of behavioral change at the  number of occurence skizofrenia at home Psychopath Surakarta become the case amount in a lot of. This Research aim to to know the influence of family support to frequency of relapsing of client skizofrenia at IGD of Mental Hospital Surakarta. This Research represent the research eksplanatory with the approach of  case study control the ( case control studies). Research location at IGD RSJ of Area Surakarta. Subyek Research as much 32 responder representing family from client with history as patient Skizofrenia within treatment 1 - 5 the last year. This research use the statistical test with linear regresi modestly. assess the linear analysis regresi modestly indicate that the family support have an effect on to frequency of relapsing of client skizofrenia in equal to 77,4% shownly by R Square 0,774 ( F : 102,880, p : 0,000). support from client family is 40,6% with the support  and 59,4% with the high support. Family Support have an effect on to frequency of relapsing of patient Skizofrenia at IGD RSJ of Area Surakarta   Keyword : Family Support, relapsing frequency, Skizofrenia